Empowering Underprivileged Women Through Digital Business Assistance in Strengthening Food Security - Az Zahra Arie Yuniar; Lilik Rahmawati (Riviera Publishing, 2024)
In this digital era, the use of information and communication technology is becoming increasingly important in accessing wider markets and increasing business competitiveness. However, many underprivileged women do not yet have the knowledge and skills to utilize digital technology in their businesses. The main aim of this program is to equip underprivileged women with the skills and knowledge needed to develop their businesses digitally, so as to increase income and food security in the family. This research uses qualitative methods with a case study approach to observe and analyze digital business assistance to increase the economic capacity of underprivileged women. Research findings show that focused and sustainable interventions in the form of digital assistance can be an effective economic empowerment strategy in improving the welfare of underprivileged communities, especially women. The implications of this research show that digital business assistance by PT PNM Mekaar Syariah has great potential in strengthening the role of women in the economy, improving family welfare, and overall having a positive impact on local and national economic growth.